Effect of Pamphlet on Knowledge Regarding Selected Anticoagulation Therapy among Cardiac Patients in Selected Hospitals in Metropolitan City - Thomas, K. Priya; Sawant, Suchita; Ancilin Allwyn, Dernit (Indian Journal of Nursing Sciences, 2024)
Introduction: Anticoagulant drugs are widely used in hospital and community settings. Anticoagulant drugs have an important role in the treatment and prevention of blood clots. Anticoagulants, which are considered “high alert medications,” can often lead to adverse drug events in the inpatient and outpatient health-care setting if not managed appropriately. Many of anticoagulation-associated adverse effects result from medication errors, suggesting they are preventable. To avoid these issues, all healthcare workers who prescribe anticoagulants need to educate the patient and the family. Aims: This study aimed to examine the effect of pamphlet on knowledge regarding selected anticoagulation therapy among cardiac patients. Materials and Methods: A descriptive evaluative research approach with one group pre-test and post-test research design was used for the study. The study was conducted at Mumbai district. The sample comprised of 50 cardiac patient who fulfilled the inclusion criteria for the sample selection. Sample was selected using non-probability convenient sampling technique. Data were analyzed using descriptive and inferential statistics. In that Paired t-test to assess the effect of pamphlet on knowledge regarding selected anticoagulation therapy among cardiac patients. Results: The result of this study showed that the pre-test the mean of the knowledge obtained by the cardiac patients was 12.600 and in posttest it increased to 21.260. It is evidence by the calculated t-value 18.877 is greater than tabulated value 2.010 at 0.05 level of significance. Conclusion: Pamphlet was effective measure to improve knowledge regarding selected anticoagulation therapy among cardiac patients.